Microbial exopolysaccharides as bioprotective polymers for plant resilience in climate-stressed agroecosystems - Huu-Thanh Nguyen; Phu-Tho Nguyen; Minh-Nhut Pham; Thi-Tho Nguyen (Agriculture and Natural Resources, 2026)
Microbial exopolysaccharides (EPS) are multifunctional polymers that play critical roles in supporting plant resilience under climate-induced environmental stress. Increasing evidence shows that EPS secreted by rhizobacteria contribute to water retention, ion chelation, antioxidant activation, immune modulation, biofilm formation and microbe-plant signaling, collectively enhancing plant tolerance to drought, salinity and soil toxicity. Despite the recognized ecological functions of EPS, knowledge of their diversity, mechanisms of action and practical applications in agriculture remains fragmented. This review synthesized current advances in understanding the structural and functional attributes of microbial EPS and highlighted representative microbial producers with plant-protective traits. Emerging applications, including EPS-based biostimulants, bioformulations, and stress-mitigation tools, were examined critically in the context of climate-smart and sustainable crop management. In addition, the discussion considered key challenges, such as variability in EPS production, lack of standardized formulations and limited field validation. By reframing microbial EPS as biologically active shields in the rhizosphere, this review underscored their potential to strengthen crop productivity and agroecosystem stability, as well as further outlining priority directions for research and policy to translate molecular insights into scalable innovations that address the challenges of climate-resilient agriculture.